An early Paleoproterozoic high-K intrusive complex in southwestern Tarim Block, NW China: Age, geochemistry, and tectonic implications - Zhang, C.; Li, Zheng-Xiang; Li, X.; Yu, H.; Ye, H. (International Association for Gondwana Research, 2007)
Systematic geochronologic, geochemical, and Nd isotopic analyses were carried out for an early Paleoproterozoic high-K intrusive complex exposed in southwestern Tarim, NW China. The results provide a better understanding of the Paleoproterozoic tectonic evolution of the Tarim Block. Zircon U–Pb age dating indicates two Paleoproterozoic magmatic episodes occurring at ca. 2.41 Ga and ca. 2.34 Ga respectively, which were followed by a ca. 1.9 Ga metamorphic event. The 2.41 Ga granodiorite–adamellite suite shares characteristics of late to post-orogenic metaluminous A-type granites in its high alkalinity (Na2O+K2O=7.6–9.3%), total REE (410–788 ppm), Zr (370–660 ppm), and Y (21.7– 58.4 ppm) contents. eNd(t) values for the suite range from -3.22 to -4.71 and accordingly the Nd modal ages (T2DM) vary between 3.05 Ga and 3.17 Ga. Based on geochemical data, the 2.34 Ga suite can be subdivided into two sub-suites, namely A-type and S-type. However, both types have comparable Nd isotope compositions (eNd(t)˜-0.41 to -2.08) and similar narrow T2DM ranges (2.76–2.91 Ga). Geochemical and Nd isotopic data for the high-K intrusive complex, in conjunction with the regional geological setting, suggest that both the 2.41 Ga suite and the 2.34 Ga A-type sub-suite might have been produced by partial melting of the Archean mafic crust in a continental rift environment. The S-type sub-suite is thought to have formed by partial melting of felsic pelites and/or metagreywackes recycled from Archean crust (TTG?). Gabbro enclaves with positive eNd(t) value (2.15) have been found to be intermingling within the 2.34 Ga suite; ca. 2.34–2.36 Ga gabbroic dykes and adamellites have previously been documented in eastern Tarim. These observations indicate that the high-K intrusions may reflect the emergence of depleted mantle upwelling beneath the Tarim Block at that time. We suggest a three-stages model for the Precambrian crustal evolution in the Tarim Block: (1) the formation of proto-crust (TTG) by ca. 2.5 Ga, (2) episodes of felsic magmatism possibly occurring in continental rift environments at ca. 2.41 Ga and ca. 2.34–2.36 Ga, and (3) ca. 1.9 Ga metamorphism that may represent the solidification of the Precambrian basement of the Tarim Block.